Evaluasi Intact Stability Offshore Support Vessel A.H.T.S Kittiwake Milik PT. Baruna Raya Logistics Ketika Mentransportasikan Muatan ke Offshore Platform - Anggoronadhi Dianiswara; Syabrina Mawaddah Warahmah (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
Oil and gas are natural resources that have an important role in global development. Oil and gas in industry develops form operation on mainland, waters, and offshore. Oil and gas exploration needs and offshore platform. Offshore platform required supporting components that are transported by Offshore Support vessel (OSV). OSV supporting transport components to the offshore platform. In transporting components, stability of OSV needs to be evaluated in accordance with applicable standards. Stability is the ability of OSV to return to its original position after getting slope. Factors that affect stability are OSV dimension and the mass of the cargo being transported. This research was conducted by evaluating the stability of OSV when intact while transporting cargo to the offshore platform. Research variations are 100% consumable (departure) and 10% consumable (Arrival). Research using Maxsurf software and follow the criteria on the DNVGL-ST-N001. The research result of intact stability in accordance with stability criteria in DNVGL-STN001 section initial GM, intact range, and area ratio under wind overturning arm.